PENGARUH KONSENTRASI PAKLOBUTRAZOL PADA PERTUMBUHAN DAN PENAMPILAN TANAMAN SEDAP MALAM (POLYANTHES TUBEROSA L.) DALAM POT - Rugayah, Rugayah; Hendarto, Kus; Ginting, Yohannes C.; Ristiani, Rina (JURNAL AGROTROPIKA, 2020)
Tuberose (Polyanthus tuberosa L.) is a popular ornamental plant in Indonesia as cut flowers and sowing flowers. It can be used as potted flowers by making the flower stalks shorter. One way to get tuberose that have criteria as potted flowers is by administering growth inhibitors using Paclobutrazol. This research was conducted at the Greenhouse of the Horticultural Building, Faculty of Agriculture, University of Lampung in November to August 2017, aimed to determine the effect of the concentration of paclobutrazol on the growth and appearance of tuberose and to determine the best concentration of paclobutrazol in the appearance of potted tuberose. This study used a randomized block design (RCBD) with a single treatment with 6 levels of paclobutrazol concentration, namely 0, 75, 150, 225, 300, and 375 ppm with 3 replications. Homogeneity of variance was tested by Bartlett test and additivity was tested by Tukey test. Then, it was continued with the F test and with the Least Significant Difference test (LSD) at the 5% level. The results showed that administration of paclobutrazol was significantly affected pseudo stem circumference and all variables of generative growth except the length of the florets. The concentration of paclobutrazol up to 375 ppm has not obtained optimum results. Keywords: Concentration, growth, paclobutrazol, tuberose